Diffusion of electric vehicles in Brazil from the stakeholders' perspective - Costa, E.; Horta, A.; Correia, A.; Seixas, J.; Costa, G.; Sperling, D. (International Journal of Sustainable Transportation, 2021)
A major challenge for humankind is to reduce global carbon dioxide (CO2) emissions to avoid the most harmful impacts of climate change. The transport sector is responsible for almost 1/4 of the world’s energy-related emissions, with road transportation representing around 1/5 of the fuel consumption. Electric vehicles (EVs) may help to reduce CO2 emissions, but their diffusion is uncertain due to market barriers. This paper investigates the electric vehicle (EV), which has a smaller ecological footprint, as an alternative capable of meeting the needs of personal transport in Brazil. To carry out this evaluation, the study considers socio-techno-economic and political-environmental-innovation aspects to assess the challenges and opportunities facing the adoption of electric vehicles. The analysis was carried out based on a survey administered to a wide range of stakeholders. A SWOT analysis was performed to understand the most critical factors affecting the future of EVs in Brazil, which is a top-ten automotive manufacturer worldwide and a leader in sugar cane ethanol production. The results suggest light-duty electric vehicles (LDEV) as a first option for low-carbon passengers’ mobility and that EVs expansion will require market regulation, incentive policies and adequate charging infrastructure. Both consumers and society in general will benefit most from the expansion of EVs due to low emissions and total cost of ownership (TCO). The results show where decision-makers should focus their attention.